A brassinosteroid functional analogue increases soybean drought resilience - Perez Borroto, Lucia Sandra; Guzzo, María Carla; Posada, Gisella Anabel; Peña Malavera, Andrea Natalia; Castagnaro, Atilio Pedro; Gonzalez Olmedo, Justo Lorenzo; Coll, Yamilet; Pardo, Esteban Mariano (Nature Research, 2022)
Drought severely affects soybean productivity, challenging breeding/management strategies to increase crop resilience. Hormone-based biostimulants like brassinosteroids (BRs) modulate growth/defence trade-off, mitigating yield losses; yet, natural molecule's low stability challenges the development of cost-effective and long-lasting analogues. Here, we investigated for the first time the effects of BR functional analogue DI-31 in soybean physiology under drought by assessing changes in growth, photosynthesis, water relations, antioxidant metabolism, nodulation, and nitrogen homeostasis. Moreover, DI-31 application frequencies' effects on crop cycle and commercial cultivar yield stabilisation under drought were assessed. A single foliar application of DI-31 favoured plant drought tolerance, preventing reductions in canopy development and enhancing plant performance and water use since the early stages of stress. The analogue also increased the antioxidant response, favouring nitrogen homeostasis maintenance and attenuating the nodular senescence. Moreover, foliar applications of DI-31 every 21 days enhanced the absolute yield by ~ 9% and reduced drought-induced yield losses by ~ 7% in four commercial cultivars, increasing their drought tolerance efficiency by ~ 12%. These findings demonstrated the practical value of DI-31 as an environmentally friendly alternative for integrative soybean resilience management under drought.